Nursing educators’ and undergraduate nursing students’ beliefs and perceptions on evidence-based practice, evidence implementation, organizational readiness and culture: An exploratory cross-sectional study - Cardoso D. (2021)
© 2021Aims: To describe the undergraduate nursing students’ and nursing educators' evidence-based practice beliefs, their extent of evidence-based practice implementation and their perspectives regarding organizational culture for evidence-based practice. To identify any relationship between the mentioned variables. Background: The integration of evidence-based practice in nursing curricula is crucial to educate nursing students to incorporate evidence-based practice in their future clinical practice. Therefore, to promote its integration within nursing education, it is important to deeply understand how prepared academic institutions are for teaching about and supporting evidence-based practice integration. Design: Cross-sectional study. Methods: Nursing educators and undergraduate nursing students from nine Portuguese nursing schools were invited to participate in this study through an electronic survey comprising socio-demographic questions and the scales. Results: Sixty-eight nursing educators replied to the survey. Most were female, have PhD and have evidence-based practice training. They showed mean scores of 88.92 ± 8.18 for evidence-based practice beliefs, 40.20 ± 18.93 for evidence-based practice implementation and 80.59 ± 17.52 for evidence-based practice organizational culture and readiness. Concerning nursing educator sample, there were moderate and statistically significant relationship between: evidence-based practice beliefs and implementation; and evidence-based practice beliefs and organizational culture and readiness for school-wide integration of evidence-based practice. Between evidence-based practice implementation and organizational culture and readiness for school-wide integration of evidence-based practice, there was a small relationship. One hundred and sixty-seven undergraduate nursing students answered the survey. Mostly, they were female and were in third or fourth year of their nursing degree. Similarly, to educators, students showed mean scores of 58.69 ± 6.92 for evidence-based practice beliefs, 32.37 ± 16.97 for evidence-based practice implementation and 84.20 ± 23.48 for evidence-based practice organizational culture and readiness. Regarding undergraduate nursing student sample, there were moderate and statistically significant relationship between the different variables. Conclusions: Both nursing educators and undergraduate nursing students had strong evidence-based practice beliefs, but low levels of evidence-based practice implementation. In nursing educators’ and undergraduate nursing students’ perspectives, there were opportunities in their schools for the development of an evidence-based practice culture. Based on results, support for development and testing of interventions, specifically tailored for promoting evidence-based practice implementation in nursing educational contexts, is recommended.